Generosity across contexts - Alexander L. Davis; John H. Miller; Roberto A. Weber (University of Zurich, Department of Economics, 2011)
Extensive research in economics explores generosity in monetary allocations, while generosity in non-laboratory contexts often involves the allocation of consumption goods or non-monetary harm. Psychological evidence suggests that generosity may be higher in such contexts. We compare generosity in decisions that vary whether allocations are monetary or non-monetary, and whether they involve utility gains or losses. In two experiments, generosity is higher in nonmonetary contexts. Thus, the typical monetary laboratory Dictator game may underestimate generosity in many non-laboratory contexts. We find a weak relationship between individuals' allocation decisions in monetary and nonmonetary contexts, but a strong relationship within monetary contexts.
Keywords: D03; D64; C91; 330; altruism; generosity; harm; experiment; Altruismus; Nichtkooperatives Spiel; Diktatur; Test